IMPLIKATUR PERCAKAPAN DI PELELANGAN IKAN KENDARI - Eko Prasetyo; Lilik Rita Lindayani; Maliudin (Program Studi Sastra Indonesia Fakultas Ilmu Budaya Universitas Halu Oleo, 2024)
This research is a qualitative descriptive study which aims to describe the lingual form of conversational implicature contained in the communication that occurs at the Kendari Fish Auction. In this study, the method used to collect data is to record conversations that occur at the Kendari Fish Auction auction, then sort through the data in which there are conversational implicature, then the data that has been collected is then analyzed. In analyzing the data, the researcher used the conversational implicature research model conducted by Prof. Dr. Ida BagusPutrayasa, M.Pd. in his book entitled Pragmatics. In this study, researchers found eight kinds of conversational implicature, which are forbid conversational implicator, approving conversational implicature, rejecting conversation implicator, commanding conversation implicator, requesting conversation implantator, affirming conversational implicator, complaining conversation implicator, offering conversational implicature Keywords: Implicative Conversation at Kendari Fish Auction